READING ALOUD STRATEGIES IN READING ENGLISH TEXTS - Nurlaelawati, Iyen; Dzulqodah, Shofa (Indonesian Journal of Applied Linguistics, 2014)
Abstract: Reading aloud by a young language learner shows unique patterns as the evidence of his/her language data processing. This study, thus, explored the strategies applied by an Indonesian young language learner to read English written texts aloud to identify errors that actually bring certain benefits in her language learning process such as making intelligent guesses when she encountered unfamiliar words. It adopted qualitative case study design involving a seven-year old girl as the subject, who had been exposed to English four yearearlier.The data were gained through observing her reading and interviewing her after reading. The data from both techniques confirmed each other and provided in-depth data analysis.Next, the data were analyzed under the the framework synthesized from Littlewood (1984). The findings indicated that to read aloud the subject made use of three strategies among others: overgeneralization, transfer and simplification. This means that the subject employed her L2 oral proficiency and L1 reading ability to process the L2 data from reading. The study implies that educators need to pay moreattention on how children process the language data they gain and to povide appropriate learning environments in order to prepare them to be better readers, beside improving awareness in similarities and differences of L1 and L2.Keywords:young learner, reading strategies, read aloud